DISTRACTION IN LEARNING: A CASE-STUDY OF MISDEMEANOUR FACTORS AMONG VOCATIONAL STUDENTS FROM TEACHER PERSPECTIVES - Suhaizal Hashim; Alias Masek; Affero Ismail; Sutarto Hadi Priyanto (Sanata Dharma University Yogyakarta, 2020)
Previous studies reported that disciplinary problems that occur amongst school students from teacher perspective; while some studies reported that this problem becomes increasingly serious and widespread, but both retract students from learning. Henceforth, this survey was conducted to investigate how far the problem occurred among vocational college students especially catering students. An interview session was conducted with several catering teachers in two vocational colleges in Southern Region of Malaysia, which focuses on three types of problems namely bullying, truancy and stealing. Data were analysed using thematic analysis using deductive approach. Result indicated that these discipline problems occur among catering students is at alarming level. Peers and students’ background contributed to students’ misdemeanours. Thus, these factors can be a starting point for further mitigating the cases and more focuses should be given on students’ learning.